Incorporating drama activities in the ESL classroom: an exploratory study / Nur Diyana A Rahman - A Rahman, Nur Diyana (2011)
This paper reports on an exploratory study designed to explore (a) students’ perceptions towards the incorporation of drama activities, (b) issues faced by the students throughout the incorporation of drama activities, and (c) the extent of communication and participation among students brought about by the use of drama activities. The convenience samples were among thirty (30) English second language learners of a General English class of Limkokwing University. The data were collected through pre and post interviews, and classroom’s observations. Analyses of the data were explained based on sub-themes, which revealed positive feedbacks in students’ perceptions towards working in groups, communicating and performing with others; as part of the incorporation of drama activities. Moreover, the issues faced by the teacher and students throughout the incorporation of drama activities were discovered. There were only two (2) students showed significant changes in their communication and participation in drama activities, while the other remaining students were still passive and not interested in communicating and participating in the drama activities.